DINAMIKA INTERAKSI ANTARA ELITE POLITIK LOKAL DAN ELITE AGAMA DALAM KONTESTASI PEMILIHAN PRESIDEN 2019 DI KOTA PASURUAN - Farid Farid; Priyatmoko Priyatmoko (Universitas Airlangga, 2020)
The study focuses on the political phenomenon of the dynamic interaction between the local political elites and the religious elites in the contestation of the 2019 presidential elections. In this case of the contestation of presidential elections 2019, each has an influential elite in the community. The subject in this study to the political elites was a member of the Regional House of Representatives and Leaders of political parties in Pasuruan City. Furthermore, regarding the religious elites, it is a religious figure or religious leader who has an educational institution or a mass. The analysis study conducted is to use the main data obtained from an interview to the subject of the researcher and the secondary data information obtained from other supporting documents. The results of the research resulted in the findings of the Interaction dynamics between local political elites and religious elites in Pasuruan City during the 2019 Presidential Election. This interaction aims to win the candidate of the 2019 presidential spouse in Pasuruan city. Religious Elites and Local political elites in Pasuruan City each have the same interests. This interest is to win each of the spouses supported presidential candidates. The local political elites and religious elites are trying to win presidential candidates in a variety of ways. It starts with an open declaration until the indirect support. The religious elites in Pasuruan City have an important role in every election activity. Therefore, in the election activities will occur the dynamic interaction between the political elites and religious elites.